Sentenced to Science : One Black Man's Story of Imprisonment in America - Hornblum, Allen M. (Book collections on Project MUSE., 2007)
"From 1951 Until 1974, Holmesburg Prison in Philadelphia was the site of thousands of experiments on prisoners conducted by researchers under the direction of University of Pennsylvania dermatologist Albert M. Kligman. While most of the experiments were testing cosmetics, detergents, and deodorants, the trials also included scores of Phase I drug trials, inoculations of radioactive isotopes, and applications of dioxin, in addition to mind-control experiments for the Army and CIA. These experiments often left the subject-prisoners, mostly African Americans, in excruciating pain and had long-term debilitating effects on their health. This is one among many episodes of the sordid history of medical experimentation on the black population of the United States." "The story of the Holmesburg trials was documented by Allen Hornblum in his 1998 book Acres of Skin. The more general history of African Americans as human guinea pigs has most recently been told by Harriet Washington in her 2007 book Medical Apartheid. The subject is currently a topic of heated public debate in the wake of a 2006 report from an influential panel of medical experts recommending that the federal government loosen the regulations in place since the 1970s that have limited the testing of pharmaceuticals on prison inmates." "Sentenced To Science retells the story of the Holmesburg experiments more dramatically through the eyes of one black man, Edward "Butch" Anthony, who suffered greatly from the experiments for which he "volunteered" during multiple terms at the prison. This is not only one black man's highly personal account of what it was like to be an imprisoned test subject, but also a sobering reminder that there were many African Americans caught in the viselike grip of a scientific research community willing to bend any code of ethics in order to accomplish its goals and a criminal justice system that sold prisoners to the highest bidder."--Jacket